South Polar chart / compiled from the latest information in the Hydrographic Department, 1949 (Great Britain. Hydrographic Office, 1949)
Depths shown by soundings.; Includes conversion table.; "Crown copyright reserved."; "116.49" -- upper right margin.; "Z/en 1949" -- lower right margin. Color;